The Sufficiency Economy Philosophy shown in Lung Yen Kon Saman Novel (Uncle Yen, the normal man) - Chuthap, Watsaranan (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2019)
This article aims to apply the principles and theories of Sufficiency Economy Philosophy to analyze Lung Yen Kon Saman novel (Uncle Yen, the normal man). The findings show that Lung Yen Kon Saman novel (Uncle Yen, the normal man) reflected 2 levels of sufficiency; sufficiency in family level and sufficiency in society. Those explained that sufficiency in family level or personal level can be seen from Yen’s ways and shaping life of Ram. For the sufficiency in society level appeared as combined forces of all sectors in the society then it took part in the development of the foundation of its culture. Those developments showed country development from building a stable foundation in the basics to create prosperity grew, respectively. Thus, Lung Yen Kon Saman novel (Uncle Yen, the normal man) is a novel which reflected society and give incestuous to readers. It suggested that the philosophy of sufficiency economy should be taken as a way to live. This is because people can build foundation of life stability, strongly and independence.